2019
DOI: 10.3389/feart.2019.00035
|View full text |Cite
|
Sign up to set email alerts
|

Chenier Morphodynamics on the Amazon-Influenced Coast of Suriname, South America: Implications for Beach Ecosystem Services

Abstract: Anthony et al. Chenier Morphodynamics and Beach Ecosystem Services turtle-nesting. Further reduction of the length of exposed chenier is apparently halted near the Suriname River mouth where mud is liquefied by the outflowing river and tidal jet, but the continued existence of this preserved beach could be endangered by sand mining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…However the sediment loads in the local rivers are minor when compared with the suspended sediment concentrations observed in coastal waters. In fact, the coast of French Guiana is part of the longest stretch of muddy coastline found worldwide and experiences drastic morphological instability due to the longshore migration of mudbanks under wave forcing [24,25]. The Maroni estuary, which separates French Guiana from Suriname, is located approximately 700 km to the northwest of the Amazon and features a mean discharge of ∼1680 m 3 s −1 [19].…”
Section: Study Sitementioning
confidence: 99%
“…However the sediment loads in the local rivers are minor when compared with the suspended sediment concentrations observed in coastal waters. In fact, the coast of French Guiana is part of the longest stretch of muddy coastline found worldwide and experiences drastic morphological instability due to the longshore migration of mudbanks under wave forcing [24,25]. The Maroni estuary, which separates French Guiana from Suriname, is located approximately 700 km to the northwest of the Amazon and features a mean discharge of ∼1680 m 3 s −1 [19].…”
Section: Study Sitementioning
confidence: 99%
“…First efforts to map and assess ES can be found on various scales in SUR (Ramirez-Gomez et al 2013;Ramirez-Gomez et al 2016;Anthony et al 2019), and FG (Roger et al 2016). However, a systematic literature review of existing MAES studies (Sieber et al 2018) revealed that there is still potential for more thorough implementation of the ES concept.…”
Section: Introductionmentioning
confidence: 99%
“…In this system, the inner part of a mud bank can weld onto the coast, creating new land that can be rapidly colonized by mangroves, whereas in inter-bank zones, higher incident wave energy can lead to intense shoreline erosion. Inter-bank erosion is mitigated, where beaches (cheniers) composed of sand and/or shells occur (Augustinus, 1978;Augustinus et al, 1989;Prost, 1989;Anthony et al, 2019). Cheniers are wave-reworked coarse-grained deposits resting stratigraphically on a muddy substrate (Otvos, 2018).…”
Section: Introductionmentioning
confidence: 99%